"Going Offline": Social Media, Source Verification, and Chinese Investigative Journalism During "Information Overload". (14th September 2021) - Xu, Nairui; Gutsche, Robert E.
ABSTRACT: Based on interviews with 25 investigative journalists in Beijing, China, this study suggests digital journalists may be increasingly challenged by a sense of "information overload" as they navigate social media and online environments crowded with dis- and mis-information, fake profiles and sources, and massive amounts of opinion journalism that is presented as professional journalism. This overload has reinforced Chinese investigative journalists' dedication to a conventional form of verification: meeting face-to-face with sources. This study contributes to scholarship on Chinese journalism by expanding knowledge about investigative journalists in the country and by complicating understandings of how journalists there work in an age of social media, disinformation, and increased interests in verification.